Recharging process of commercial floating-gate MOS transistor in dosimetry application. (November 2021) - Ilić, Stefan D.; Andjelković, Marko S.; Duane, Russell; Palma, Alberto J.; Sarajlić, Milija; Stanković, Srboljub; Ristić, Goran S.
Abstract: We investigated the recharging process of commercial floating gate device (EPAD) during the six different dose rates and ten irradiation cycles with the highest dose rate. Dose rate dependence of the floating gate dosimeter was observed from 1 Gy/h to 26 Gy/h ( H 2 O ). There is no change of the dosimetric characteristic with a constant dose rate of 26 Gy/h for ten cycles. The absorbed dose does not affect the drift of the threshold voltage readings after the irradiation steps. The reprogramming characteristic is not degrading with the absorbed dose for the ten irradiation cycles, giving the promising potential in the application for dosimetric purposes. Highlights: Sensitivity increases with the dose rate. No change in dosimetric characteristics for ten recharging cycles. The minimum detectable dose has calculated to be 52 mGy (H2 O).